Sistemática e biogeografia de Oligoneuriidae Ulmer, 1914 (Insecta: Ephemeroptera) - Massariol, Fabiana Criste (2017)
Oligoneuriidae is a Pantropical Family of Ephemeroptera composed by 12 genera and 62 species. Three subfamilies are recognized, Chromarcyinae with a single species from Oriental Region, Colocrurinae with two fossil species from Brazil, and Oligoneuriinae with the remainder species distributed in Americas, Afrotropical and Palearctic regions. Their immature stage inhabits a wide variety of aquatic environments with different levels of disturbance. As a consequence, Oligoneuriidae species could be used as bioindicator however their taxonomy is somewhat complex once nymphs and adults do not show many diagnostic morphological characteristics and most species have not been described based on all stages of the life cycle. In this context, the use of DNA barcodes becomes a useful and complementary tool for traditional taxonomy. As a result of the present thesis, six new species were described — L. alcidesi, L. aldinae, O. (O.) amandae, O. (O.) mitra, O. (Y.) anatina, and O. (Y.) truncata — and the subgenera Madeconeuria and Yawari were raised at the generic level, so the family now has 14 genera and 68 species. The parsimony analysis of the morphological data and the maximum likelihood and bayesian inference of the molecular and combined data supports the division into three subfamilies. In addition, based on the clusters recovered in all analyzes, three new tribes were proposed: Homoeoneuriini, Elassoneuriini, and Oligoneuriellini. According to biogeographic analyses (S-DIVA and Lagrange) and divergence time estimation analysis Oligoneuriidae originated about 150 Mya on the Gondwan continent, but restrict to Neotropical Region. 97 sequences representing 73% of living genera and 20% of the described species of Oligoneuriidae were deposited in BOLD in a new project called “DNA Barcoding of Oligoneuriidae”. The maximum intraspecific divergence value was high (15.05%), which may be related to the presence of cryptic species. Despite the existence of a local DNA barcode, a global DNA barcode was not detected for Oligoneuriidae.